PELAKSANAAN PERCERAIAN DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN MENURUT HUKUM KANONIK - Heribertus Richard Chascarino (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2022)
The purpose of this study is to find out how divorce is viewed from the point of view of the positive law of the Republic of Indonesia and the canonical law of the catholic church, and how the process is carried out. This study uses a normative juridical method by analyzing the articles in the legislation related to the problem being studied.The results of the study reveal that there are contradictory contradictions, where the positive law in our country expressly allows and regulates the issue of divorce between husband and wife, but this is actually inversely proportional to the law of the Catholic church which is embraced by all Catholics in the world, where the catholic church absolutely forbids divorce between catholic husband and wife. The Catholic Church does not recognize the existence of divorce, but in the teaching of the Catholic Church what is known is the annulment of marriage.